The covid-19 pandemic in vulnerable communities: the responses of Rio de Janeiro’s favelas - Dalia Maimon Schiray (Association Recherche & Régulation, 2021)
This article analyses the effectiveness of public-health and economic-policy responses of the Brazilian government to the pandemic during the year 2020. We show that prevention, following WHO guidelines, is more easily adopted by the middle class. In low-income groups, housing conditions, lack of sanitation and informality limit the effectiveness of prevention. Governance problems in the relationship between the federal government and the states and municipalities have reduced the effectiveness of these measures. Brazil continues to fight the world’s second-highest number of deaths, after the United States. In this context, the article focuses on the responses of Rio de Janeiro’s favelas to the pandemic during and after the lockdown. With no specific policy on the part of the Brazilian government, this vulnerable population, supported by social organization present in the communities, adopted health preventive measures and benefited from donations of food and hygiene products that minimized the announced tragedy.